Personal innovativeness and facilitating conditions in shaping the outlooks toward m-banking adoption among generation Y in Malaysia - Foo-Wah Lim; Ahmad Fakhrorazi; Ridho Bramulya Ikhsan; Karina Silitonga; Wei-Kit Loke; Nik Abdullah (International Journal of Electrical and Computer Engineering (IJECE), 2023)
The study investigated the determinants of m-banking adoption among generation Y (Gen-Y) in Malaysia. The study underpinned the technology acceptance model as the main guideline or a blueprint for analyzing the research model. The study applied a survey research design and investigated structural equation modeling (SEM) under the partial least-square SEM (PLS-SEM) technique using SmartPLS 2.0. A total 358 m-banking users in Malaysia were exerted as respondents who were randomly selected and then investigated. The results of the analysis conducted with PLS-SEM reveal the existence of usage convenience, facilitating conditions, and personal innovation in information technology that has been remarkably influenced by the outlooks that have adopted m-banking in the country of Malaysia. In addition, the usage convenience that has been felt and facilitated by the conditions found can affect the appraised practicality of m-banking remarkably. Finally, the usage convenience of m-banking that is felt among Gen-Y in Malaysia is influenced by the remarkable activation of personal conditions and innovations exerted in information technology.